2015
DOI: 10.1007/s10517-015-2905-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conditioned Medium and Bone Marrow Stem Cell Lysate on the Course of Acetaminophen-Induced Liver Failure

Abstract: A composition containing culture medium conditioned by mesenchymal stem cells and mesenchymal stem cell lysate improves biochemical parameters, reduces inflammation, and stimulates regenerative processes in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In the present study, we found that mice treated with BML/CTX showed a 1.5-fold increase in the total numbers of macrophages in their spleens despite the decrease in the total numbers of iPMN and mPMN in PBL and spleen. The beneficial effects of BML are also supported by stimulating effects of BMC from leukopenic animals by influencing the homeostasis of the hematopoietic compartment through transient lymphodepletion followed by rebound replenishment of immune cells pools [ 33 ]. This could explain our results of better mobilization of myeloid cells by BML/CTX than BML/PBS.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that mice treated with BML/CTX showed a 1.5-fold increase in the total numbers of macrophages in their spleens despite the decrease in the total numbers of iPMN and mPMN in PBL and spleen. The beneficial effects of BML are also supported by stimulating effects of BMC from leukopenic animals by influencing the homeostasis of the hematopoietic compartment through transient lymphodepletion followed by rebound replenishment of immune cells pools [ 33 ]. This could explain our results of better mobilization of myeloid cells by BML/CTX than BML/PBS.…”
Section: Discussionmentioning
confidence: 99%
“…Our study analyzed the improvement of liver functions (ALT, TIBL, ALB, and PT) after MSCT and the impact of MSCT on MELD score characterized by immune tolerance of stem cells [ 54 ]. All of them can provide a systematic review of MSC application in LF patients.…”
Section: Discussionmentioning
confidence: 99%
“…They may indifferently stimulate the proliferation of both normal cells and mutated cells, which are naturally selected for their high proliferation potential. They possess anti-apoptotic activity, which reduces tissue damage by inhibiting apoptosis and promotes regeneration (Albersen et al, 2010;Khubutiya et al, 2015;Hsu et al, 2018). Furthermore, MSC lysates expose soluble factors to tissues without allowing live cells to act directly on host tissues, which amplifies their positive effects.…”
Section: Function and Application Of Msc Lysatesmentioning
confidence: 99%